Clinical picture of toxocariasis in children in the Lodz region - Niedworok, Małgorzata; Sordyl, Beata; Płaneta-Małecka, Izabela; Borecka, Anna; Gawor, Jakub; Małecka-Panas, Ewa (Przewodnik Lekarza/Guide for GPs, 2008)
Toxocariasis is a Toxocara canis or a T. cati larval infection, which circulates in the body and reaches various human organs and tissues, resulting in uncharacteristic symptoms depending on the number of consumed larvae, location in the body, duration of infection, condition of the host’s immune system and frequency of reinfection. Two main toxocariasis clinical syndromes have been described: visceral larva migrans (VLM) syndrome and ocular larva migrans (OLM) syndrome. Recently, additionally covert, asymptomatic toxocariasis and central nervous system toxocariasis are being recognized. The study objective was description of the clinical course of toxocariasis in children in the Lodz region. Among children suffering from toxocariasis in 1 child VLM, in 122 children covert and in 55 children asymptomatic toxocariasis have been diagnosed. Diffuse abdominal pain was the most frequent symptom in children with toxocariasis.